TIL DARSLARIDA MADANIYATNI QAMRAB OLISH (Scientific journal of the Fergana State University, 2023)
The paper aims at showing the importance of culture in teaching foreign languages and offers some strategies to be used while embedding culture in language classroom. In the article some attitudes towards involving culture in language classrooms by experts are discussed. Moreover, the problems associated with teaching culture are discussed and the reasons pose those problems are pointed out.  As language is developed within the culture, culture is also widely delivered by language, they are indispensible from each other which should be equally emphasized in teaching languages. In the article some techniques are suggested to be involved in language classrooms to achieve language proficiency and improve the student knowledge regarding the target culture.